Metafora Konseptual dalam Rubrik Unak-Anik Kahirupan Majalah Online Manglé : Analisis Semantik Kognitif - Aulia, Zakia Nurfitri; Nur, Tajudin (LOKABASA, 2020)
This study aims to reveal the types of conceptual metaphors, conceptual meanings, and image scheme at unak anik kahirupan writing in Manglé electronic magazine.This type of research includes qualitative research that is descriptive analysis.  A cognitive semantic conceptual study of Lakoff and Johnson (1980) supported by Cruse Croft (2004) are used to describe and analyze the data. This study used descriptive method in which the data source were got from unak anik kahirupan writing in Manglé electronic magazine in the February 2020 edition. The result show that there are twelve (12) data which classified based on type of metaphors. First, there are four (4) data of struktural  metaphors with various conceptual meanings, such as pioneer, supporter, education stage, and specialist. Second, there are four (4) data of orientational metaphors with various conceptual meanings, such as influence, feeling, and enhancement. The last, there are four (4) data of ontological metaphors with various conceptual meanings, such as relation, teaser, process, and defense. Furthermore, that data has six (6) type of  image scheme, such as identity (matching), excistence (process),unity (link), force (restraint, attraction, counter force), container  (content),  and Space (up-down).AbstrakPenelitian ini bertujuan untuk mengungkapkan jenis metafora konseptual, makna konseptual, dan skema citra dalam penulisan unak-anik kahirupan majalah online manglé. Jenis penelitian ini termasuk penelitian kualitatif yang bersifat analisis deskriptif. Metode deskriptif dan kajian konseptual semantik kognitif Lakoff Johnson (2003) dan Cruse Croft (2004)) yang digunakan untuk mendeskripsikan dan menganalisis data yang bersumber dari data tulisan di dalam majalah online manglé edisi bulan Februari tahun 2020. Hasil analisis ditemukan terdapat dua belas (12) data yang diklasifikasikan berdasarkan jenis metafora. Pertama, terdapat empat (4) buah data metafora struktural dengan makna konseptual kader, penyemangat, jenjang pendidikan, dan ahli; Kedua, terdapat empat (4)  buah data metafora orientasional dengan makna konseptual pengaruh, perasaan, dan proses; dan terakhir, terdapat empat (4) buah data metafora ontologis dengan makna konseptual hubungan, pemikat, proses, dan pertahanan. Data tersebut pun memiliki enam (6) buah jenis skema citra, yaitu identitas ‘identity’ (matching), eksistensi ‘excistence’ (process), kesatuan ‘unity’(link), kekuatan ‘force’ (restraint, attraction, counter force), wadah ‘container’ (content), Ruang ‘Space’ (up-down).